Baseline tissue levels of trace metals and metalloids to approach ecological threshold concentrations in aquatic macroinvertebrates. (August 2018) - Rodriguez, Pilar; Méndez-Fernández, Leire; Pardo, Isabel; Costas, Noemi; Martinez-Madrid, Maite
Graphical abstract: Highlights: Metal baseline range of values for reference river benthic communities is provided. The 90 percentile (P90) of the baseline data is assessed as ecological threshold. Metal P90 values for each taxon are used as estimates of no-observed-effect levels. The approach is in compliance with the European EQS directive for biota. Ecological threshold tissue concentrations varied by taxon and feeding group. Abstract: Within the framework of the European Environmental Quality Standards Directive, the biota was recognized as a suitable matrix for monitoring water quality. In the Nalón River basin (North Spain), a catchment subject to historical mining activities, ten macroinvertebrate taxa (4 mayflies, 1 perlid stonefly, 2 caddisflies, 2 oligochaete worms, and 1 blackfly) were collected from unpolluted reference sites in the study area, and the sites were assessed as having High or Good ecological status based on their macroinvertebrate communities to establish a metal bioaccumulation reference condition. For each taxon, tissue concentrations of seven metals (Cd, Cr, Cu, Hg, Ni, Hg, and Zn) and two metalloids (As and Se) were measured and interpreted as natural baseline tissue concentrations that reflected the natural variability of the region. The taxa selected as biomonitors represented 5 different feeding styles in the benthic community: deposit-feeders, scrapers, filterers, generalists and predators, and bioaccumulation was analyzed both by taxon and feeding style as well as general habits (endo- vs epi-benthic) and river type. For each taxon, ecological threshold tissue concentrations (ETTC) were calculated as the 90th percentile (P90) of the baseline data distribution. In most instances, the deposit-feeders (aquatic lumbricid and microdrile oligochaetes) showed the highest ETTCs, except for Cu and Zn, which were mainly bioaccumulated by generalist Ephemerellidae, followed by scraper Heptageniidae in the case of Cu. The P90 values were derived from organisms in unaltered reference conditions as estimates of the no-observed-effect concentrations (NOEC), and should provide an approach to ETTCs for the field macroinvertebrate taxa of the region below which the alteration of the benthic community is unlikely. For each metal and metalloid, the P90s for the 10 taxa were entered in a species-sensitivity-distribution model, and the median hazard concentration (HC50 ) for the macroinvertebrate community was calculated. The ecological threshold concentrations in the biota calculated in this study are proposed for use as a screening tool in the environmental risk assessment of the Nalón River basin and the Cantabrian region, allowing metal exceedance in the selected biomonitors to further research using other lines of evidence under the European Water Framework directive.